Evidence from priming on how L2 sentence processing impacts L3 production and cross-linguistic awareness - Michelotti, Anna; Engemann, Helen (Frontiers in Language Sciences, 2025)
In the present study we investigate L2-to-L3 priming of motion event (ME) constructions in L1 German learners of English (L2) and Italian (L3). This is a domain in which foreign language (FL) learners often have difficulties adapting to target language norms, especially when the preferential typological encoding patterns of source and target language differ. We adopted a pre-/post-test design to address the question of whether priming affects cross-linguistic awareness of the L3 target structure. This design allowed us to investigate whether and how L2 processing impacts L3 production and cross-linguistic awareness in the learners' L3. The results provide strong evidence that processing ME constructions in the L2 leads to activation of the relevant constructions in the target L3. Our findings provide less conclusive evidence for the occurrence of implicit learning. Concerning cross-linguistic awareness, a numerical trend suggests a weak improvement from the pre-test to the post-test, although no significant effect of priming intervention was found. Our findings indicate that targeted exposure to the L2 has a significant impact on learners' L3. We consider this as further evidence that previously acquired L2s can be used as a strategic resource in the acquisition of additional languages. These findings are thus relevant not only for psycholinguistic research but also for foreign language didactics.